COMPARATIVE EDUCATION IN THE EDUCATIONAL SYSTEMS AND PROBLEMS IN LIKENESSES AND DIFFERENCES BETWEEN REGIONS OF THE WORLD - Steinbach, Monica; Afroozeh, Shahrzad (SCAD Independent, 2016)
This paper is to consider the term ?comparative? in its more restricted sense, in the way the term is used in various comparative fields of study. It is somewhat curious that scholars in our field of comparative education have never attempted to sort out the various meanings of the term ?comparative.? I do not plan to draw a firm distinction between the two spheres, though it might be helpful to suggest that ?comparative education? is generally regarded as the more academic or scientific aspect of the field, while international education is related to ?cooperation, understanding, and exchange? elements of the field. I feel we must reject the hegemonic claims of science. We recall, for example, that Comte believed society traversed through various stages, from religion, to philosophy, then to science. His mistake, from my vantage point, was to place these ways of knowing in a hierarchical framework, which makes philosophy a second-rate means of knowing, and religion a third-rate means of knowing. My own orientation is to place them parallel with each other. There is a place for the spiritual, a place for the philosophical, and a place for the scientific, and any attempt to place one exclusively over the other is inappropriate.